STRATEGI PENGEMBANGAN POTENSI WISATA AIR PANAS DI DESA LUOK MANIPI SEBAGAI DAYA TARIK WISATA YANG BERKELANJUTAN - Moh Affandi B. Djanan; Ansar Ansar; Saskia Arman; Nurhalisa Nurhalisa; Fatimah Fatimah (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Luok Manipi Village, Tolitoli Regency, has a potential for hot spring tourism that has great potential to be developed as a leading tourist destination based on local potential. However, the utilization of this potential has not been optimally managed due to limited supporting infrastructure, minimal promotion, and low community involvement in tourism management. This community service activity aims to increase the capacity of the community and village government in managing hot spring tourism potential sustainably through mentoring, strategic planning, and strengthening local institutions. The service implementation method uses a participatory approach with the stages of field observation, interviews, focus group discussions (FGDs), and assistance in developing tourism development strategies based on SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The results of the activity show an increase in community understanding and participation in tourism management, the formulation of a hot spring tourism development strategy that includes improving basic facilities, digital-based promotion, and strengthening collaboration between the community, village government, and relevant stakeholders. This community service activity is expected to encourage the development of sustainable village tourism, improve the local community economy, and maintain environmental sustainability around the hot spring tourism area of ​​Luok Manipi Village.